Influence of sex on results and consequences of coronary fractional flow reserve in clinical practice: results of a prospective large-scale multicenter registry. (3rd October 2022) - Troebs, M; Marwan, M; Gaede, L; Moellmann, H; Giesler, T; Rittger, H; Rudolph, T; Pauschinger, M; Moshage, W; Brueck, M; Achenbach, S
Abstract: Background: Measurement of fractional flow reserve (FFR) is clinically indicated in order to assess the hemodynamic relevance of coronary artery lesions and determine the need for revascularization. Preliminary data sugest that there may be significant differences regarding use and outcome of FFR measurements in men versus women. Purpose: We therefore analyzed the influence of sex on FFR values and treatment consequences in a large-scale, prospective multicenter registry of consecutive patients undergoing clinically indicated FFR measurements in the setting of chronic or acute coronary syndromes. Methods: In a large, multicenter prospective registry of patients undergoing FFR, the relationship of stenosis degree to FFR, the influence of FFR on revascularization decisions were compared between male and female patients. (clinicaltrials.gov NCT03055910) Results: A cohort of 2000 patients from 8 centers was evaluated (73% male, 27% female, median age 69±10 years, 15% acute coronary syndromes). The median number of interrogated lesions was 2 in male and 2 in female patients. A total of 2958 lesions were interrogated by FFR (2156 male, 802 female; 67 LM, 1722 LAD, 646 LCX, 523 RCA). Median stenosis degree was 60% (IQR 50%-70%) in male and, identically, 60% (IQR 50%-70%) in female patients. All the same, median measured FFR values were 0.86 (IQR 0.81–0.92) in male and 0.89 (IQR 0.84–0.93) in female patients (p<0.001). Of all lesions interrrogated, 488/2156 (23%) in men and only 100/802 (12%) in women displayed an FFR value ≤0.80 (p<0.001). The median stenosis degree of lesions with an FFR value ≤0.80 was 70% (IQR 60–80%) in men and 70% (IQR 65–84%) in women (n.s.). In multivariable analysis, stenosis degree, lesion location in LAD, ACS culprit lesion, and male sex were independent predictors of an FFR value ≤0.80. The overall rate of revascularization was 24% in men and 14% in women (p<0.001), driven by lower FFR values in men. In lesions with FFR values ≤0.80, revascularization rate was 94% both in men and in women (n.s.). Conclusion: Female sex is independently associated with higher FFR values when used to determine the hemodynamic relevance of coronary lesions in the setting of chronic or acute coronary syndromes. Independent of stenosis degree, FFR measurements are significantly less frequently followed by revascularization in women. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): St. Jude Medical